Primary squamous cell carcinoma of the ovary. Review of the literature - Luo, Yan; Bian, Ce (Frontiers in Oncology, 2022)
Pure primary ovarian squamous cell carcinoma (oSCC) is very rare, about 42 cases have been reported in the literature. Due to lack of effective treatment guidelines, its prognosis is very poor. Here, we report a 52-year-old postmenopausal woman was diagnosed with pure primary oSCC in our center and underwent debulking surgery followed by chemotherapy with carboplatin, paclitaxel and bevacizumab regimen. Died of tumor progression and multiple organ failure on 11 months subsequent to surgery.